The early Islamic glass from Ṣīr Banī Yās, UAE - Phelps, Matt; Simpson, St John; Freestone, Ian C. (Proceedings of the Seminar for Arabian Studies, 2018)
Detailed studies of the pottery and stuccoes of the church and associated complex at Ṣīr Banī Yās indicate they date to the seventh and eighth centuries. This paper examines the only other significant set of finds, namely the glassware. Several other churches and monasteries have been excavated in the Persian Gulf and western desert of Iraq, but this is the first occasion when the glass assemblage has been studied in detail and has included a comprehensive scientific analysis of the glass compositions. Analysis by electron probe microanalysis of eighty-five samples has identified four compositional groups. The largest is relatively high in lime and alumina, and could not be related to previously analysed groups. Two groups are compositionally like Mesopotamian glass of the Sasanian and early Islamic periods, corresponding to Mesopotamian Types 1 and 2 of Phelps (2016), and suggest trade in glass from Mesopotamia to Ṣīr Banī Yās. A final group is small and shares similarity to three contemporaneous samples from Kush. The sparse use of manganese oxide (MnO) as a decolourant in the glass as opposed to its ubiquitous use in ninth-century Abbasid glass suggests an early Islamic seventh- to eighth-century date for this assemblage, consistent with the ceramic dating.